Prawnomiędzynarodowe koncepcje ekorozwoju - Janina Ciechanowicz (Wydział Prawa i Administracji UAM, 1996)
The article presents the basic premises of eco-development policy in law and economy, the European conceptions of eco-development and a global view of international concepts of eco-development - with particular focus on the "Rio de Janeiro Declaration", the "Global Action Programme", the "Bergen Declaration" (1990), the "Programme for Protection of the Baltic Sea", the "New Helsinki Convention" (1992), the "Programme of Action for Environment Protection in Central and Eastern Europe" (EAP, 1993). Against this background the author discusses Poland's policies and legislation in the matter, and examines the practical and legal problems of adjusting Polish norms to the obligatory law of the European Union.
Legal and international conceptions of eco-development